Orbitofrontal cortex volume and intrinsic religiosity in non-clinical psychosis - Pelletier-Baldelli, Andrea (2014)
Research indicates that religiosity plays a complex role in mental illness. Despite this link, little work has been done to clarify the role of religiosity in persons exhibiting non-clinical psychosis (NCP, individuals experiencing fleeting psychotic-like symptoms in the absence of a formal psychotic disorder). Further, there are no NCP investigations into whether abnormalities exist in brain structures that are associated with religiosity. Understanding these relationships in NCP is important to clarify the role of religiosity and brain structural anomalies in psychosis. Twenty individuals experiencing NCP and twenty controls were assessed for intrinsic religiosity (IR; motivation/commitment to religious beliefs and/or practices) using a well-validated self-report scale. Structural magnetic resonance imaging was used to determine volumes of the orbitofrontal cortex (OFC), a critical region that has been associated with increased religiosity. Results indicate that IR is elevated in the NCP group, and that these individuals exhibit bilateral volume reduction in both the lateral and medial OFC. Sample-wide correlations are non-significant, but show notable relationships between smaller OFC regions and increased IR. Significant negative relationships were found between OFC volume and depressive and negative symptoms. Overall, results suggest that brain abnormalities associated with NCP may also confer a heightened susceptibility for religiosity.